Lexical Ambiguity in English Puns on Memes Posted by X Account @Punhubonline: English - Delia Azzahra Ulya Huluqiah; Irman Nurhapitudin; Ruminda (Journal of English Development, 2025)
Memes are a recent way to communicate, particularly popular on social media platforms such as X. Many memes engage readers by combining text with images or videos. An important component contributing to a meme's humor is using ambiguity in puns. This phenomenon demonstrates its importance for readers to comprehend the meaning and function of puns in memes. Nevertheless, despite the growing use of memes as a communication medium, limited study has studied the particular role of lexical ambiguity in generating humor within digital media. This research aims to identify the various types of lexical ambiguity employed in puns portrayed in memes posted by the @Punhubonline X account and examine the impact of these ambiguities on the development of humor. A qualitative descriptive methodology was applied to examine the research data, which consisted of 20 data of recent memes from the account. The various types of lexical ambiguity are identified using Ullmann's theory, and how it produces of humor is described using Kant's theory. Findings indicate that 15 words or phrases demonstrate lexical ambiguity of the polysemy type, while 5 words or phrases demonstrate the homophone type. The conclusion exists that the appropriate application of lexical ambiguity can produce entertainment content in the digital medium of the current day. The employment of lexical ambiguity in memes enables current digital content users to present entertaining content on social media in a more engaging and creative way, providing people to acquire both entertainment and novel knowledge